Sport related concussion – Potential for biomarkers to improve acute management. (October 2018) - Costello, Daniel M; Kaye, Andrew H; O'Brien, Terence J; Shultz, Sandy R
Highlights: Mild traumatic brain injury. Chronic traumatic encephalopathy. Concussion management. Concussion biomarkers – MRI, blood. Abstract: Sport-related concussion is a common form of mild traumatic brain injury that is now recognised as a serious health issue. Growing evidence suggests concussion may result in long-term and severe neurological disabilities. Recent research into the diagnosis and management of concussion may provide new approaches to concussion management that limit the potential long-term adverse effects of concussion. This paper summarises the problem of sport-related concussion and reviews key factors (sex, age, genetics) that may modify concussion outcomes. Current sport-related concussion tools are described. Analysis of emerging methods of acute concussion diagnosis using objective fluid and neuroimaging biomarkers is provided. These new concussion biomarkers have the potential to change management of sport-related concussion.